Correlation between severe acute respiratory syndrome coronavirus 2 infection and serum anti-neutrophil cytoplasmic antibody formation - Huang, Hao; Zang, Yu-Jie; Li, Zheng-Guo; Li, Qian; Ma, Chun-Yan; Zhao, Hai-Yuan; Li, Hang (Frontiers in Immunology, 2025)
ObjectiveTo investigate the impact of SARS-CoV-2 infection on the formation of antineutrophil cytoplasmic antibodies (ANCA).MethodsSerum samples from 154 patients infected with SARS-CoV-2 were collected and tested for ANCA and antinuclear antibodies (ANA) using indirect immunofluorescence assay (IFA). Enzyme-linked immunosorbent assay (ELISA) was used to confirm the target antigens in ANCA fluorescence-positive samples. Eighty-seven healthy individuals were selected as the control group. Statistical analysis was performed using SPSS 26.0 software, with P < 0.05 considered statistically significant.ResultsThe ANCA fluorescence positivity rate in the control group (1.1%) was not significantly different from that in COVID-19 positive patients (2.5%) (χ² = 0.574, P > 0.05). Among COVID-19 positive patients, 4 cases (2.5%) were ANCA fluorescence positive, while 10 cases (6.4%) were ANA positive. The difference between these two rates was not statistically significant (χ² = 2.694, P > 0.05).ConclusionThe Omicron variant of SARS-CoV-2 has minimal association with the formation of serum ANCA.